Effect of Conditional Cash Transfer Program on the Scholastic Performance of High School Students in Naga City - Competente, Ronnel Joseph (JPAIR Multidisciplinary Research, 2019)
Conditional cash transfer (CCT) programs, as for the Naga City, Philippines, include the Pantawid Pamilyang Pilipino Program (4Ps) and Quality Elementary and High School Education in Naga (QUEEN), both aimed to help students to have access to education and also improve its quality. The study sought to describe the effect of CCT programs on the scholastic performance of 237 students in a secondary school in Naga City, Philippines. Using a correlational descriptive design, the author analyzed the dropped-out rate and generally weighted averages of students. Results revealed that CCT has no effect in reducing the dropped-out rate and no significant difference in academic performance among the beneficiaries and non-beneficiaries of the CCT.